Moisture-friction dual-mode power generation device and application thereof
By integrating moisture and triboelectric power generation modules into a moisture-triboelectric dual-mode power generation device, and using composite aerogel materials and organic ionic hydrogels, the limitations of MEG and TENG applications under different humidity conditions have been overcome, achieving high power density energy harvesting and stable output.
Patent Information
- Application Number
- CN202411334195.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-24
AI Technical Summary
Existing wet electric generators (MEGs) and triboelectric nanogenerators (TENGs) each have their own application limitations under low and high humidity conditions, making it difficult to achieve high power density energy harvesting, and the differences in device structure make it difficult to design hybrid devices.
A moisture-triboelectric dual-mode power generation device is designed by integrating a moisture power generation module and a triboelectric power generation module and sharing the same power generation material. A composite aerogel material, including two-dimensional nanosheets, nanofibers and hydrophilic polymers, is used to construct a layered structure and oriented pore network. Combined with organic ionic hydrogel and inserted electrodes, parallel coupling of the circuit connector is achieved.
It achieves high-performance power harvesting under different humidity conditions, improves current and voltage output, enhances the mechanical properties and stability of the device, simplifies production and installation, reduces costs, and facilitates mass production.
Smart Images

Figure CN119298708A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of new energy power generation, and in particular relates to a moisture-friction dual-mode power generation device and applications thereof. Background Art
[0002] In order to alleviate the environmental pollution and energy crisis caused by the massive consumption of fossil fuels, the development and utilization of renewable energy and sustainable energy have become important research contents in today's energy field. Converting environmental energy into electrical energy provides a practical and sustainable solution to alleviate energy and environmental problems. Wet electric generator (MEG) and triboelectric nanogenerator (TENG) are two emerging energy harvesting technologies that can alleviate the energy crisis, especially promote the development of distributed energy and the Internet of Things.
[0003] MEG can spontaneously harvest electrical energy from the atmosphere through the interaction between hygroscopic materials and moisture, providing a sustainable power generation strategy with the advantage of high current output, but with application limitations under low humidity conditions. TENG provides an emerging technology for converting low-frequency mechanical energy into electrical energy, with the advantage of high voltage, but also has drawbacks such as low current output, humidity sensitivity, and mechanical durability. Combining these two strategies into a hybrid device (MEG-TENG) can reconcile voltage and current output to achieve a high power density energy harvester. Due to the structural differences between the two devices and the high humidity sensitivity of TENG, it remains a challenge to design a hybrid MEG-TENG energy harvesting system with a reasonable device structure. Summary of the invention
[0004] In view of the defects of the prior art, the technical problem to be solved by the present invention is to provide a moisture-friction dual-mode power generation device and its application.
[0005] The present invention provides a moisture-friction dual-mode power generation device, which comprises: a moisture power generation module and a friction power generation module; the moisture power generation module and the friction power generation module are integrated by inserting electrodes and share the same power generation material; the moisture power generation module also comprises an organic ion hydrogel, which is arranged on the lower surface of the power generation material; the composite aerogel is a composite aerogel constructed of nanosheets, nanofibers and hydrophilic polymers.
[0006] Preferably, the nanosheet is a two-dimensional nanosheet.
[0007] The two-dimensional nanosheet is one or more of graphene oxide (GO), MXene, montmorillonite (MMT), and molybdenum disulfide (MoS2).
[0008] Further preferably, the two-dimensional nanosheet is MXene, and the MXene is Ti3C2Tx, wherein x is 0-2.
[0009] Preferably, the nanofibers are one or more of cellulose nanofibers (CNFs), aramid nanofibers (ANFs), and silk nanofibers (SNFs);
[0010] Further preferably, the cellulose is: cellulose nanofiber (CNF);
[0011] Further preferably, the cellulose nanofiber (CNF) is: TEMPO oxidized cellulose nanofiber (TCNF);
[0012] The hydrophilic polymer is one or more of polyvinyl alcohol (PVA), polyacrylic acid (PAA) and polyethylene glycol (PEG).
[0013] Further preferably, the hydrophilic polymer is: polyvinyl alcohol (PVA);
[0014] The unique structural characteristics of the power generation material of the present invention and the physical / chemical characteristics of the raw materials endow the composite aerogel with the feasibility of being a shared power generation material for a wet gas power generation system and a friction power generation system.
[0015] The composite aerogel power generation material can meet the requirements of both the MEG system and the TENG system.
[0016] Preferably, the mass ratio of nanofibers to flexible hydrophilic polymers in the composite aerogel is 100:1 to 1:100; the mass ratio of nanosheets to nanofibers is 10:1 to 1:100;
[0017] Further preferably, in the composite aerogel, the mass ratio of the nanofibers to the flexible hydrophilic polymer is 10:1 to 1:10; and the mass ratio of the nanosheets to the nanofibers is 1:1-50.
[0018] Preferably, the composite aerogel has a layered microstructure with a directional pore network between the layers.
[0019] Furthermore, the layered and directional pore structure of the composite aerogel can better dissipate the stress generated during compression, providing more reliable mechanical support and shape recovery. In addition, the hydrophilic polymer can be combined with the nanofibers by physical mixing or chemical modification to further improve the mechanical flexibility and hydrophilicity of the composite aerogel.
[0020] Furthermore, the negatively charged nanofibers, as nanocarriers, can form a "brick-and-mortar" interlayer bond with the two-dimensional nanosheets through hydrogen bond self-assembly, which can make the layered structure of the composite aerogel more compact and orderly, further improving its mechanical properties and stability. At the same time, this interlayer bond can prevent the self-stacking effect of the nanosheets, thereby enhancing the ion selectivity and ion diffusion rate within the nanosheet layer.
[0021] Furthermore, the continuous oriented and ordered microchannels can effectively adsorb and migrate moisture, achieving complementary power collection of moisture and triboelectricity.
[0022] Preferably, the directional pores are one of fully or semi-through micropores, nanopores, and micro / nano composite pores, and the directional pores are highly directional and arranged along the vertical direction; the vertical direction is that the pores of the aerogel are perpendicular to the surface of the organic ion hydrogel.
[0023] Preferably, the composite aerogel preparation method is a sol-gel method, a combination of hydrothermal synthesis / sol-gel technology, 3D printing, gel polymerization, or gel casting. Further preferably, the aerogel preparation method is a sol-gel method.
[0024] Preferably, the preparation method of the composite aerogel comprises: stirring the nanofibers and the hydrophilic polymer solution uniformly, then adding the nanosheets, stirring and degassing, transferring the obtained sol to a mold for gelation to obtain a pre-gel, and then freezing and drying to obtain the composite aerogel;
[0025] Alternatively, the nanofibers and the hydrophilic polymer solution are stirred evenly, and then the nanosheets are added, stirred evenly, 3D printed, frozen and dried to obtain the composite aerogel.
[0026] Furthermore, the nanofibers are added in the form of nanofiber sol, nanofiber dispersion or nanofiber suspension; wherein the solvent in the nanodispersion or suspension includes one or more of deionized water, hexafluoroisopropanol (HFIP) and dimethyl sulfoxide (DMSO).
[0027] Furthermore, the solvent of the hydrophilic polymer solution is one or more of deionized water, ethanol, glycerol, acetic acid, and ethyl acetate.
[0028] Furthermore, the nanosheets are added in the form of a nanosheet suspension or a nanosheet dispersion, wherein the solvent comprises one or more of deionized water, ethanol, glycerol, acetic acid, ethyl acetate, and dimethyl sulfoxide (DMSO).
[0029] More preferably, the solvent is deionized water.
[0030] Preferably, the freezing is directional freezing.
[0031] Preferably, the drying method is supercritical drying, freeze drying, vacuum drying, atmospheric pressure drying, microwave drying. Further preferably, the drying method is freeze drying.
[0032] The wet gas power generation module is formed by closely fitting and connecting the organic ion hydrogel directly adhered to the power generation material and the bottom electrode to form a wet gas power generation module with the upper electrode.
[0033] Preferably, the organic ion hydrogel component comprises a gel network matrix material, an inorganic salt and a solvent; wherein the mass of the gel network matrix material is 5% to 60% (wt%) of the mass of the solvent, and the mass of the inorganic salt is 0.01% to 20% (wt%) of the total mass of the solution.
[0034] Preferably, the gel network matrix material includes any one of polyacrylamide (PAM), polyacrylamide (PAM) / polyvinyl alcohol (PVA), polyacrylamide (PAM) / gelatin (GA), polyacrylamide (PAM) / polystyrene sulfonic acid (PSSA); the inorganic salt includes one or more of LiCl, NaCl, MgCl2, AlCl3, KCl, CaCl2, and CoCl2.
[0035] More preferably, the inorganic salt is any one of LiCl, NaCl and KCl.
[0036] Preferably, the solvent is a mixed solvent of an organic solvent and water; the organic solvent includes one or more of ethylene glycol, glycerol, and dimethyl sulfoxide; and the mass percentage of water in the mixed solvent is 0.1 to 99.9%.
[0037] Furthermore, the gel network material in the organic ion hydrogel is any one of a single-component gel network of polyacrylamide (PAM), a two-component gel network of polyacrylamide (PAM) / polyvinyl alcohol (PVA), polyacrylamide (PAM) / gelatin (GA), and polyacrylamide (PAM) / polystyrene sulfonic acid (PSSA).
[0038] Preferably, the organic ion hydrogel is disposed on the lower surface of the power generation material: the organic ion hydrogel and the power generation material are directly adhered, such as applying the organic ion hydrogel to the bottom of the composite aerogel.
[0039] The method for preparing an organic ion hydrogel comprises: mixing and stirring raw materials containing a gel network matrix material monomer, a solvent, a crosslinking agent, and an initiator, adding an inorganic salt, mixing evenly, and curing under an ultraviolet lamp for 1-30 minutes to obtain an organic ion hydrogel. The crosslinking agent is one or more of N,N-methylenebisacrylamide (MBAA), polyisopropylacrylate (MBA), and benzoyl peroxide (BPO); the mass ratio of the crosslinking agent to the gel network monomer is 1:10 to 1:500; the initiator is one or more of α-ketoglutaric acid, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methylacetone, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-acetone, and 2-hydroxy-2-methylphenylpropiotone; the mass ratio of the initiator to the gel network monomer is 1:10 to 1:500.
[0040] Preferably, the insertion electrodes include a bottom electrode of the wet gas power generation module, an upper electrode of the wet gas power generation module and a lower electrode of the friction power generation module.
[0041] Preferably, the inserted electrode is one or more of an ITO glass electrode, a FTO glass electrode, a TCO glass electrode, and a metal electrode, wherein the metal electrode is any one of Al, Zn, Fe, Cu, Ag, etc. Further preferably, the bottom inserted electrode is an Al electrode.
[0042] Preferably, the friction power generation module further comprises a friction contact electrode (upper electrode of the friction power generation module), wherein the friction contact electrode is arranged directly above the power generation material;
[0043] Preferably, the moisture-friction dual-mode power generation device further comprises a circuit connector, wherein the circuit connector is a rectifier circuit, wherein the rectifier circuit couples the rectified AC output and DC output in parallel.
[0044] The circuit connector couples the rectified AC output and DC output in parallel to achieve synchronous collection of wet gas power generation and friction power generation energy.
[0045] Preferably, the friction contact electrode comprises a conductive tape and a friction functional layer; wherein the conductive tape comprises one or more of a conductive cloth tape, a conductive silicone tape, and a conductive metal tape; the conductive component in the conductive tape comprises one or more of platinum, gold, silver, copper, nickel, aluminum, carbon materials, graphene, MXene, carbon nanotubes, and conductive polymers; the friction functional layer material comprises one or more of polytetrafluoroethylene (PTFE), polyperfluoroethylene propylene (FEP), polydimethylsiloxane (PDMS), polyvinylidene fluoride-co-hexafluoropropylene (PVDF-HFP), polyvinylidene fluoride (PVDF), polypropylene (PP), polyethylene terephthalate (PET), styrene propylene copolymer, styrene butadiene copolymer, synthetic fiber, polymethacrylate, polyvinyl alcohol (PVA), polyethylene glycol (PEG), polyester, polyisobutylene, polyethylene terephthalate, chloroprene rubber, butadiene propylene copolymer, natural rubber, polyacrylonitrile, acrylonitrile vinyl chloride, stainless steel sheet, iron sheet, copper sheet, and silver sheet.
[0046] More preferably, the friction functional layer is one of polytetrafluoroethylene (PTFE), polyfluoroethylene propylene (FEP), and polyvinylidene fluoride (PVDF).
[0047] More preferably, the friction functional layer and the power generation material in the same power generation system are made of different materials.
[0048] The present invention provides an application of the moisture-friction dual-mode power generation device in the fields of environment, energy, information and national defense.
[0049] Preferably, the application in the environmental field includes at least one of autonomous collection of environmental energy and application of intelligent environmental detection equipment; the application in the energy field includes at least one of triboelectric energy collection, piezoelectric energy collection, moisture energy collection, autonomous utilization of environmental energy, and quantitative sensing applications; the application in the information field includes at least one of the application of environmental perception, sensing and information interaction equipment; the application in the defense field includes the application of electrical power supply or power generation equipment in extreme environments.
[0050] The present invention provides a composite aerogel power generation material with a layered structure and directional pore arrangement, which has good mechanical properties, excellent hygroscopicity and efficient moisture transfer, so that the hybrid MEG-TENG device can synergistically collect electricity from moisture and mechanical energy. In a first aspect of the present invention, a composite aerogel power generation material with a vertical ordered pore structure and a preparation method thereof are provided. The composite aerogel is made of nanofibers, two-dimensional nanosheets and flexible polymers as raw materials and is constructed by directional freeze-drying technology.
[0051] The layered and directional pore structure of the composite aerogel can better dissipate the stress generated during the compression process, and can meet the needs of the power generation materials in the TENG module to withstand harsh deformation and repeated compression without structural collapse. The "brick and mud" interlayer bonding formed between the nanofibers and nanosheets can further improve its mechanical properties and stability. In addition, the introduction of two-dimensional nanosheets can improve the dielectric properties of the composite aerogel system, thereby improving the triboelectric output during the TENG process.
[0052] In the MEG module, the directional porous structure of the aerogel provides many microchannels for the transmission of moisture and ions, which helps to establish moisture and ion gradients and makes it possible for long-term stable output of MEG. A double-layer structure of MEG is constructed by directly adhering organic ion hydrogel to the surface of the power generation material, which overcomes the dependence of MEG on environmental humidity. In addition, the introduction of active ions into the gel can solve the problem of insufficient total ions in ionized water and can effectively increase the current output. The electronegative nanochannels improve the selectivity and diffusion rate of cations, further improving the performance output of MEG. The MEG module achieves high-performance output under various humidity conditions and has excellent environmental flexibility.
[0053] The present invention provides a dual-mode power generation system based on sharing the same power generation material, wherein the circuit connector couples the rectified AC output and DC output in parallel, thereby realizing the synchronous collection of MEG and TENG energy generated by the power generation material described in the first aspect. The unique design of the material microstructure and the physical / chemical properties of the material ensure the output stability of the dual-mode power generation system.
[0054] According to the research results of the present invention, a composite aerogel power generation material that can meet the needs of friction power generation and wet gas power generation has been developed, and the wet electric module and the friction electric module are integrated and share the same power generation material, realizing the synchronous collection of the coupled output of MEG-TENG.
[0055] Beneficial Effects
[0056] The power generation material involved in the present invention has a special design of layered structure and directional arrangement of pores. Its components and structural properties are highly controllable, universal, and have great potential for large-scale production, which effectively ensures the excellent electrical performance and application potential of the dual-mode power generation system.
[0057] The dual-mode power generation system developed by the present invention adopts a simple design and technology to realize the coordinated integration and coupled output of humidity power generation and friction power generation in the system. The basic components of the dual-mode power generation system are only the power generation unit and the connector, and the installation of the power generation unit and the connector is simple and convenient. The method has low requirements for experimental equipment, low production cost, assembly cost, and later maintenance cost, is easy to mass produce, and has broad application prospects.
[0058] The dual-mode power generation system provided by the present invention has the characteristics of cleanliness, sustainability, convenience, strong environmental adaptability, etc. It can be applied to power supply of electrical appliances or large-scale power generation equipment, and has high economic, environmental and social benefits and practical application potential. The excellent electrical performance and practical applicability are of great significance to the research and development of green and sustainable power sources. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 The vertical cross-sectional surface (A) and cross-sectional scanning electron microscope image (B) of the CPM-aerogel power generation material prepared by directional freezing in Example 2;
[0060] Figure 2 is a compression cycle diagram of the CPM-aerogel prepared by directional freezing as described in Example 2;
[0061] Figure 3 is a schematic diagram of the dual-mode power generation system of the present invention;
[0062] Figure 4 The voltage (A) and current coupling output diagram (B) of the dual-mode power generation system based on CPM-aerogel power generation materials in Example 2;
[0063] Figure 5 This is a voltage output diagram of the dual-mode power generation system based on CPM-aerogel power generation materials in Example 2 within 1000 cycles (humidity: 90%);
[0064] Figure 6 This is a diagram of charging a commercial capacitor based on the voltage coupling output of the dual-mode power generation system of APM-aerogel power generation materials in Example 9;
[0065] Figure 7 is a voltage output diagram of a MEG power generation module (humidity: 20%) based on CPM-aerogel power generation material in Example 10; DETAILED DESCRIPTION
[0066] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0067] Related raw materials:
[0068] Polyvinyl alcohol (PVA), polyacrylic acid (PAA), and polyethylene glycol (PEG) were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; montmorillonite (MMT) was purchased from Guangxi Ningming Mining Co., Ltd., graphene oxide (GO) and molybdenum disulfide (MoS2) were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; oxidized cellulose nanofibers (TCNF) were purchased from Shansi Technology Co., Ltd., aramid nanofibers (ANF) were purchased from Shandong Jufang New Materials Co., Ltd., and silk nanofibers (SNFs) were purchased from Nanjing Tianlu Nanotechnology Co., Ltd.;
[0069] MAX phase precursor powder (Ti3AlC2 powder) was purchased from Foshan Xinxi Technology Co., Ltd. The purity of the MAX phase precursor powder is ≥99.9%, and the particle size of the MAX phase precursor powder is 400 mesh.
[0070] The preparation method of the MXene dispersion selected in the embodiment is:
[0071] MAX powder was slowly added to a uniform mixture of LiF and HCl and stirred at 40 °C for 36 h to obtain a MXene (Ti3C2Tx) suspension. The suspension was then repeatedly washed with deionized water until the pH of the supernatant was about 7. Finally, the supernatant was ultrasonically treated to obtain a Ti3C2Tx dispersion, which was then stored in a refrigerator for later use.
[0072] Note: The directional freezing involved in the embodiments and comparative examples is vertical freezing from bottom to top.
[0073] Example 1
[0074] like Figure 2 As shown, the wet gas-friction dual-mode power generation device includes: a rectifier circuit (connector), a wet gas power generation module and a friction power generation module; the wet gas power generation module and the friction power generation module are integrated by inserting electrodes and share the same power generation material; the wet gas power generation module is also provided with an organic ion hydrogel, and the organic ion hydrogel is arranged on the lower surface of the power generation material; the friction power generation module is also provided with a friction contact electrode, wherein the friction contact electrode is arranged directly above the power generation material;
[0075] The power generation material is a composite aerogel of two-dimensional nanosheets, nanofibers and hydrophilic polymers.
[0076] The inserted electrodes include, from bottom to top, the bottom electrode of the wet gas power generation module, the upper electrode of the wet gas power generation module and the lower electrode of the friction power generation module; the bottom electrode of the wet gas power generation module is arranged at the bottom of the organic ion hydrogel; the upper electrode of the wet gas power generation module and the lower electrode of the friction power generation module are both arranged in the power generation material; the friction contact electrode is arranged directly above the power generation material;
[0077] The inserted electrode is one or more of an ITO glass electrode, a FTO glass electrode, a TCO glass electrode, and a metal electrode; the rectifier circuit couples the rectified AC output and the DC output in parallel.
[0078] Working method:
[0079] (1) The friction contact electrode is adhered to the surface of the pressure sensor by insulating tape, and the moisture-friction dual-mode power generation device is placed vertically directly below the friction contact electrode. The mechanical pressure of the friction power generation unit is provided by a linear motor (0-100N).
[0080] (2) The rectifier circuit is directly connected to a commercial multimeter (Keithley 6510) / capacitor to measure / collect the power output of the dual-mode power generation device.
[0081] Example 2
[0082] In this embodiment, a TCNF / PVA / MXene (CPM)-aerogel power generation material is provided, and its preparation method is as follows: a certain amount of PVA solution (5wt%) is added to the TCNF sol (1wt%), wherein the mass ratio of PVA to TCNF is 1:1. Then weigh a certain amount of MXene dispersion and add it to the above TCNF / PVA sol, wherein the mass ratio of MXene to TCNF is 1:4. After stirring evenly (2h) and degassing, the CPM sol is poured into a mold for gelation for 2h, and liquid nitrogen is used as a refrigerant for directional freezing (-100℃) for 0.5h. After being completely frozen, it is freeze-dried for 24h to obtain a CPM-aerogel power generation material (height 10mm) with a layered structure and directional full-penetration micro / nano composite multi-level pores.
[0083] In this embodiment, a polyacrylamide (PAM) single-component network organic ion hydrogel is used as the power source for wet gas power generation, and its preparation method is as follows: 1.5g acrylamide, 30mg N,N'-methylenebisacrylamide (MBAA), 30mg α-ketoglutaric acid are added to 10g glycerol / water mixed solvent (water mass ratio 50%), the mixed solution is stirred for 30min, and then 0.75g KCl is added and stirred for 1h to obtain a PAM-KCl pre-solution. The prepared solution is drop-casted in a mold that meets the required size, and then cured under ultraviolet light for 10min to obtain a PAM-KCl organic ion hydrogel. Then the PAM-KCl organic ion hydrogel is applied to the bottom of the CPM-aerogel for standby use.
[0084] In this embodiment, the bottom electrode of the wet gas power generation module is an Al electrode, and the upper electrode is a Cu electrode; the lower electrode of the friction power generation module is a Cu electrode, and the friction contact electrode is composed of a conductive cloth tape and polytetrafluoroethylene (PTFE), with a mechanical stress of 20N and a mechanical compression of 60%. In this case, the voltage coupling output of the dual-mode power generation system based on CPM-aerogel power generation material is 120V, and the current output is 180μA ( Figure 4 ). And the dual-mode power generation system can maintain a stable voltage output of 120V in 1000 cycles under high humidity (90%). Figure 5 ).
[0085] Example 3
[0086] In this embodiment, an ANF / PAA / GO (APO)-aerogel power generation material is provided, and the preparation method thereof is as follows: a certain amount of PAA solution (5wt%) is added to an ANF aqueous suspension (1wt%), wherein the mass ratio of PAA to ANF is 1:1. Then a certain amount of GO dispersion is weighed and added to the above-mentioned ANF / PAA sol, wherein the mass ratio of GO to ANF is 1:2. After stirring evenly (2h) and degassing, the APO sol is poured into a mold for gelation for 2h, and directional freezing (-100°C) is performed for 0.5h using liquid nitrogen as a refrigerant. After being completely frozen, it is freeze-dried for 24h to obtain an APO-aerogel power generation material (height 12mm) with a layered structure and directional full penetration of micro / nano composite multi-level pores.
[0087] In this embodiment, polyacrylamide (PAM) single-component network organic ion hydrogel is used as the power source for wet power generation, and its preparation method is as follows: acrylamide monomer (1.5g), polyisomethacrylate (MBA) crosslinker (50mg) and 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methylacetone initiator (60mg) are added with 10g ethylene glycol / water mixed solvent (water mass ratio 20%), the mixed solution is stirred for 30min, and then 0.5g LiCl is added and stirred for 1h to obtain PAM-LiCl pre-solution. The prepared solution is drop-casted in a mold that meets the required size, and then cured under ultraviolet light for 10min to obtain PAM-LiCl organic ion hydrogel. Then the PAM-LiCl organic ion hydrogel is applied to the bottom of the APO-aerogel for standby use. In this embodiment, the bottom electrode of the wet gas power generation module is an Al electrode, and the upper electrode is a Cu electrode; the lower electrode of the friction power generation module is an Ag electrode, and the friction contact electrode is composed of a conductive copper tape and polyperfluoroethylene propylene (FEP), with a mechanical stress of 10N and a mechanical compression of 40%. In this case, the voltage coupling output of the dual-mode power generation system based on the APO-aerogel power generation material is 96V, and the current output is 155μA.
[0088] Example 4
[0089] In this embodiment, a CPM-aerogel power generation material is provided, and its preparation method is as follows: add a certain amount of PVA solution (10wt%) to TCNF sol (5wt%), wherein the mass ratio of PVA to TCNF is 2:1. Then weigh a certain amount of MXene dispersion and add it to the above TCNF / PVA sol, wherein the mass ratio of MXene to TCNF is 1:50, stir evenly (2h), and obtain TCNF / PVA ink. Use a 3D printer to print the TCNF / PVA ink (the nozzle diameter is 0.41mm, the printing speed is set to 3mm / s, and the ink flow rate is 3.2mL / h) into a mold with a filling density of 30% (2.0×2.0×0.5cm 3 The printed samples were directly frozen (-100°C) for 0.5 h using liquid nitrogen as a cryogen. After the samples were completely frozen, they were freeze-dried for 24 h to obtain CPM-aerogel power generation materials (15 mm) with a layered structure and directional fully penetrating micropores.
[0090] In this embodiment, a polyacrylamide (PAM) single-component network organic ion hydrogel is used as the power source for wet gas power generation, and its preparation method is as follows: 1.5g acrylamide, 20mg N,N'-methylenebisacrylamide (MBAA), 25mg α-ketoglutaric acid are added to 10g glycerol / water mixed solvent (water mass ratio 50%), the mixed solution is stirred for 30min, and then 0.75g KCl is added and stirred for 1h to obtain a PAM-KCl pre-solution. The prepared solution is drop-casted in a mold that meets the required size, and then cured under ultraviolet light for 10min to obtain a PAM-KCl organic ion hydrogel. Then the PAM-KCl organic ion hydrogel is applied to the bottom of the CPM-aerogel for standby use.
[0091] In this embodiment, the bottom electrode of the wet gas power generation module is an Al electrode, and the upper electrode is a Cu electrode; the lower electrode of the friction power generation module is a Cu electrode, and the friction contact electrode is composed of a conductive cloth tape and polytetrafluoroethylene (PTFE), with a mechanical stress of 20N and a mechanical compression of 60%. In this case, the voltage coupling output of the CPM-aerogel-based dual-mode power generation system is 90V and the current output is 145μA.
[0092] Example 5
[0093] In this embodiment, a TCNF / PEG / MMT (TPT)-aerogel power generation material is provided, and its preparation method is as follows: add a certain amount of PEG solution (5wt%) to TCNF sol (1wt%), wherein the mass ratio of PEG to TCNF is 10:1. Then weigh a certain amount of MMT dispersion and add it to the above TCNF / PEG sol, wherein the mass ratio of MMT to TCNF is 1:1. After stirring evenly (5h) and degassing, pour the TPT sol into a mold and perform directional freezing (-50°C) for 0.5h using low-temperature ethanol as a refrigerant. After being completely frozen, freeze-dry it for 24h to obtain a TPT-aerogel power generation material (height 10mm) with a layered structure and directional full-penetrating micropores.
[0094] In the present embodiment, polyacrylamide (PAM) / polyvinyl alcohol (PVA) two-component network organic ion hydrogel is used as the power source of wet power generation, and its preparation method is as follows: 1g acrylamide, 0.5g PVA, 50mg benzoyl peroxide (BPO) crosslinking agent, 50mg 2-hydroxy-2-methyl propiophenone are added to 15g ethylene glycol / water mixed solvent (water mass ratio 50%), the mixed solution is stirred for 30min, and then 0.5g CaCl2 is added and stirred for 1h to obtain PAM / PVA-CaCl2 pre-solution. The prepared solution is drop-casted in a mold that meets the required size, and then cured under ultraviolet light for 15min to obtain PAM / PVA-CaCl2 organic ion hydrogel. Then the PAM / PVA-CaCl2 organic ion hydrogel is applied to the bottom of the TPT-aerogel for standby use.
[0095] In this embodiment, the bottom electrode of the wet gas power generation module is an FTO glass electrode, and the upper electrode is an ITO glass electrode; the lower electrode of the friction power generation module is a Cu electrode, and the friction contact electrode is composed of a conductive cloth tape and polyperfluoroethylene propylene (FEP), with a mechanical stress of 10N and a mechanical compression of 50%. In this case, the voltage coupling output of the TPT-aerogel-based dual-mode power generation system is 98V and the current output is 142μA.
[0096] Example 6
[0097] In this embodiment, a SNF / PVA / GO (SPG)-aerogel material power generation material is provided, and its preparation method is as follows: silk fibers are immersed in HFIP solution at a mass ratio of 1:20, and are fully stirred (60°C, 24h) to obtain silk microfiber (SMF) slurry. Finally, the SMF / water mixture is subjected to ultrasonic treatment (60min) and centrifugation (10000rpm, 20min) to obtain a SNF dispersion (1wt%). A certain amount of PVA solution (2wt%) is added to the SNF dispersion (1wt%), wherein the mass ratio of PVA to SNF is 1:2. A certain amount of GO dispersion is then weighed and added to the above-mentioned SNF / PVA sol, wherein the mass ratio of GO to SNF is 1:2. After stirring evenly (2h) and degassing, the SPG sol is poured into a mold and gelled for 5h under water bath conditions (50°C), and placed in a refrigerator (-20°C) and directly frozen for 24h. After being completely frozen, the sample was immersed in ethanol for thawing and solvent replacement to form an alcohol gel, and liquid nitrogen was used as a cryogen for directional freezing (-100°C) for 0.5h. After being completely frozen, it was freeze-dried for 24h to obtain an SPG-aerogel power generation material (12mm high) with a layered structure and directional semi-penetrating micro / nano composite multi-level pores.
[0098] In this embodiment, polyacrylamide (PAM) / polystyrene sulfonic acid (PSSA) two-component organic ion hydrogel is used as the power source for wet gas power generation, and its preparation method is as follows: 1g acrylamide, 0.5g PSSA, 30mg N,N'-methylenebisacrylamide (MBAA), 20mg α-ketoglutaric acid are added to 10g dimethyl sulfoxide / water mixed solvent (water mass ratio 50%), the mixed solution is stirred for 30min, and then 0.5g CoCl2 is added and stirred for 1h to obtain PAM / PSSA-CoCl2 pre-solution. The prepared solution is drop-casted in a mold that meets the required size, and then cured under ultraviolet light for 20min to obtain PAM / PSSA-CoCl2 organic ion hydrogel. Then the PAM / PSSA-CoCl2 organic ion hydrogel is applied to the bottom of the SPG-aerogel for standby use.
[0099] In this embodiment, the bottom electrode of the wet gas power generation module is a Cu electrode, and the upper electrode is a Cu electrode; the lower electrode of the friction power generation module is a Cu electrode, and the friction contact electrode is composed of a conductive cloth tape and polyvinylidene fluoride-co-hexafluoropropylene (PVDF-HFP), with a mechanical stress of 20N and a mechanical compression of 60%. In this case, the voltage coupling output of the SPG-aerogel-based dual-mode power generation system is 106V and the current output is 152μA.
[0100] Example 7
[0101] In this embodiment, a TCNF / PVA / MoS2 (TPM)-aerogel material power generation material is provided, and its preparation method is as follows: add a certain amount of PVA solution (5wt%) to the TCNF sol (1wt%), wherein the mass ratio of PVA to TCNF is 1:1. Then weigh a certain amount of MoS2 dispersion and add it to the above TCNF / PVA sol, wherein the mass ratio of MoS2 to TCNF is 1:4. After stirring evenly (2h) and degassing, pour the TPM sol into a mold for gelation for 2h, and use low-temperature ethanol as a refrigerant for directional freezing (-30℃) for 12h. After being completely frozen, freeze-dry it for 24h to obtain a TPM-aerogel power generation material (6mm high) with a layered structure and directional semi-penetrating micro / nano composite multi-level pores.
[0102] In this embodiment, polyacrylamide (PAM) organic ion hydrogel is used as the power source of wet gas power generation, and its preparation method is as follows: acrylamide monomer (1.5g), MBAA crosslinking agent (50mg), 50mg 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-acetone add 15g ethylene glycol / glycerol / water mixed solvent (water mass ratio 50%), stir the mixed solution for 30min, then add 0.5g MgCl2 and stir for 1h to obtain PAM-MgCl2 pre-solution. The prepared solution is drop-casted in a mold that meets the required size, and then cured under ultraviolet light for 20min to obtain PAM-MgCl2 organic ion hydrogel. Then the PAM-MgCl2 organic ion hydrogel is applied to the bottom of the TPM-aerogel for standby use.
[0103] In this embodiment, the bottom electrode of the wet gas power generation module is a TCO glass electrode, and the upper electrode is a Cu electrode; the lower electrode of the friction power generation module is an Ag electrode, and the friction contact electrode is composed of a conductive silicone tape and polyethylene terephthalate (PET), with a mechanical stress of 50N and a mechanical compression of 60%. In this case, the voltage coupling output of the TPM-aerogel-based dual-mode power generation system is 105V and the current output is 156μA.
[0104] Example 8
[0105] In this embodiment, a TCNF / PVA / GO (CPG)-aerogel power generation material is provided, and its preparation method is as follows: add a certain amount of PVA solution (5wt%) to TCNF sol (1wt%), wherein the mass ratio of PVA to TCNF is 1:1. Then weigh a certain amount of GO dispersion and add it to the above TCNF / PVA sol, wherein the mass ratio of GO to TCNF is 1:4. After stirring evenly (2h) and degassing, pour the CPG sol into a mold for gelation for 2h, and use liquid nitrogen as a refrigerant for directional freezing (-100℃) for 0.5h. After being completely frozen, freeze-dry it for 24h to obtain a CPG-aerogel power generation material (10mm high) with a layered structure and directional full-penetration micro / nano composite multi-level pores.
[0106] In this embodiment, a polyacrylamide (PAM) single-component network organic ion hydrogel is used as the power source for wet gas power generation, and its preparation method is as follows: 1.5g acrylamide, 30mg N,N'-methylenebisacrylamide (MBAA), 30mg α-ketoglutaric acid are added to 10g glycerol / water mixed solvent (water mass ratio 50%), the mixed solution is stirred for 30min, and then 0.75g KCl is added and stirred for 1h to obtain a PAM-KCl pre-solution. The prepared solution is drop-casted in a mold that meets the required size, and then cured under ultraviolet light for 10min to obtain a PAM-KCl organic ion hydrogel. Then the PAM-KCl organic ion hydrogel is applied to the bottom of the CPG-aerogel for standby use.
[0107] In this embodiment, the bottom electrode of the wet gas power generation module is an Al electrode, and the upper electrode is a Cu electrode; the lower electrode of the friction power generation module is a Cu electrode, and the friction contact electrode is composed of a conductive cloth tape and polytetrafluoroethylene (PTFE), with a mechanical stress of 20N and a mechanical compression of 60%. In this case, the voltage coupling output of the dual-mode power generation system based on CPG-aerogel power generation material is 98V, and the current output is 162μA.
[0108] Example 9
[0109] In this embodiment, an ANF / PVA / MXene (APM)-aerogel material power generation material is provided, and its preparation method is as follows: 0.5g of commercial ANF nanofibers and 1g of KOH are added to 1g of DMSO, and magnetic stirring is performed at room temperature for 24h to obtain an ANF solution (20wt%). A certain amount of PVA solution (2wt%) is added to the ANF solution, wherein the mass ratio of PVA to ANF is 2:1. Then a certain amount of MXene dispersion is weighed and added to the above-mentioned ANF / PVA sol, wherein the mass ratio of MXene to ANF is 1:1. After stirring evenly (2h) and degassing, the APM sol is poured into a mold for gelation for 2h, and liquid nitrogen is used as a refrigerant for directional freezing (-196℃) for 0.5h. After being completely frozen, it is freeze-dried for 36h to obtain an APM-aerogel power generation material (8mm high) with a layered structure and directional full penetration of micro / nano composite multi-level pores.
[0110] In this embodiment, a polyacrylamide (PAM) single-component network organic ion hydrogel is used as a power source for wet gas power generation, and its preparation method is as follows: 1.5g acrylamide, 30mg N,N'-methylenebisacrylamide (MBAA), and 50mg α-ketoglutaric acid are added to 10g ethylene glycol / glycerol / water mixed solvent (water mass ratio 60%), and the mixed solution is stirred for 30min, and then 0.25g AlCl3 is added and stirred for 1h to obtain a PAM-AlCl3 pre-solution. The prepared solution is drop-casted in a mold that meets the required size, and then cured under ultraviolet light for 10min to obtain a PAM-AlCl3 ion hydrogel. Then the PAM-AlCl3 ion hydrogel is applied to the bottom of the APM-aerogel for standby use.
[0111] In this embodiment, the bottom electrode of the wet gas power generation module is a Zn electrode and the upper electrode is a Cu electrode; the lower electrode of the friction power generation module is a Cu electrode, and the friction contact electrode is composed of a conductive cloth tape and polypropylene (PP), with a mechanical stress of 20N and a mechanical compression of 60%. In this case, the APM-aerogel-based dual-mode power generation system is directly connected to a commercial capacitor through an external circuit, which can charge the capacitor (4.7μF) ( Figure 6 ).
[0112] Example 10
[0113] In this embodiment, a TCNF / PVA / MXene (CPM)-aerogel power generation material is provided, and its preparation method is as follows: a certain amount of PVA solution (5wt%) is added to a commercial TCNF sol (1wt%), wherein the mass ratio of PVA to TCNF is 1:1. Then weigh a certain amount of MXene dispersion and add it to the above TCNF / PVA sol, wherein the mass ratio of MXene to TCNF is 1:4. After stirring evenly (2h) and degassing, the CPM sol is poured into a mold for gelation for 2h, and liquid nitrogen is used as a refrigerant for directional freezing (-100℃) for 0.5h. After being completely frozen, it is freeze-dried for 24h to obtain a CPM-aerogel power generation material (2mm) with a layered structure and directional full-penetration micro / nano composite multi-level pores.
[0114] In this embodiment, a polyacrylamide (PAM) single-component network organic ion hydrogel is used as the power source for wet gas power generation, and its preparation method is as follows: 1.5g acrylamide, 30mg N,N'-methylenebisacrylamide (MBAA), 30mg α-ketoglutaric acid are added to 10g glycerol / water mixed solvent (water mass ratio 50%), the mixed solution is stirred for 30min, and then 0.6g KCl is added and stirred for 1h to obtain a PAM-KCl pre-solution. The prepared solution is drop-casted in a mold that meets the required size, and then cured under ultraviolet light for 10min to obtain a PAM-KCl organic ion hydrogel. Then the PAM-KCl organic ion hydrogel is applied to the bottom of the CPM-aerogel for standby use.
[0115] In this embodiment, the bottom electrodes of the wet gas power generation module are Al electrodes and the upper electrodes are Cu electrodes. The MEG power generation unit based on CPM-aerogel power generation material can achieve stable voltage output within 4 minutes under low humidity (20%), and the MEG power generation is 0.8V ( Figure 7 ).
[0116] Comparative Example 1
[0117] In this embodiment, a TCNF / PVA / MXene (CPM)-aerogel power generation material is provided, and its preparation method is as follows: a certain amount of PVA solution (5wt%) is added to the TCNF sol (1wt%), wherein the mass ratio of PVA to TCNF is 1:1. Then weigh a certain amount of MXene dispersion and add it to the above TCNF / PVA sol, wherein the mass ratio of MXene to TCNF is 1:4. After stirring evenly (2h) and degassing, the CPM sol is poured into a mold for gelation for 2h, and then placed in a refrigerator for freezing for 24h. After being completely frozen, it is freeze-dried for 24h to obtain a CPM-aerogel power generation material (10mm high) with non-directional semi-penetrating micron pores.
[0118] In this embodiment, a polyacrylamide (PAM) single-component network organic ion hydrogel is used as the power source for wet gas power generation, and its preparation method is as follows: 1.5g acrylamide, 30mg N,N'-methylenebisacrylamide (MBAA), 30mg α-ketoglutaric acid are added to 10g glycerol / water mixed solvent (water mass ratio 50%), the mixed solution is stirred for 30min, and then 0.75g KCl is added and stirred for 1h to obtain a PAM-KCl pre-solution. The prepared solution is drop-casted in a mold that meets the required size, and then cured under ultraviolet light for 10min to obtain a PAM-KCl organic ion hydrogel. Then the PAM-KCl organic ion hydrogel is applied to the bottom of the CPM-aerogel for standby use.
[0119] In this embodiment, the bottom electrode of the wet gas power generation module is an Al electrode, and the upper electrode is a Cu electrode; the lower electrode of the friction power generation module is a Cu electrode, and the friction contact electrode is composed of a conductive cloth tape and polytetrafluoroethylene (PTFE), with a mechanical stress of 20N and a mechanical compression of 60%. In this case, the voltage coupling output of the dual-mode power generation system based on CPM-aerogel power generation material is 90V, and the current output is 56μA.
[0120] Comparative Example 2
[0121] In this embodiment, a TCNF / PVA-aerogel power generation material is provided, and the preparation method thereof is as follows: a certain amount of PVA solution (5wt%) is added to the TCNF sol (1wt%), wherein the mass ratio of PVA to TCNF is 1:1. After stirring evenly (2h), the TCNF / PVA sol is poured into a mold for gelation for 2h after degassing, and directional freezing (-100℃) is performed for 0.5h using liquid nitrogen as a refrigerant. After being completely frozen, it is freeze-dried for 24h to obtain a TCNF / PVA-aerogel power generation material (10mm) having multi-level pores that penetrate the micro / nano composite.
[0122] In this embodiment, a polyacrylamide (PAM) single-component network organic ion hydrogel is used as the power source for wet gas power generation, and its preparation method is as follows: 1.5g acrylamide, 30mg N,N'-methylenebisacrylamide (MBAA), 30mg α-ketoglutaric acid are added to 10g glycerol / water mixed solvent (water mass ratio 50%), the mixed solution is stirred for 30min, and then 0.75g KCl is added and stirred for 1h to obtain a PAM-KCl pre-solution. The prepared solution is drop-casted in a mold that meets the required size, and then cured under ultraviolet light for 10min to obtain a PAM-KCl organic ion hydrogel. Then the PAM-KCl organic ion hydrogel is applied to the bottom of the TCNF / PVA-aerogel for standby use.
[0123] In this embodiment, the bottom electrode of the wet gas power generation module is an Al electrode, and the upper electrode is a Cu electrode; the lower electrode of the friction power generation module is a Cu electrode, and the friction contact electrode is composed of a conductive cloth tape and polytetrafluoroethylene (PTFE), with a mechanical stress of 20N and a mechanical compression of 60%. In this case, the voltage coupling output of the dual-mode power generation system based on TCNF / PVA-aerogel power generation material is 80V, and the current output is 36μA.
Claims
1. A moisture-friction dual-mode power generation device, characterized in that: The wet gas-friction dual-mode power generation device comprises: a wet gas power generation module and a friction power generation module; the wet gas power generation module and the friction power generation module are integrated by inserting electrodes and share the same power generation material; the wet gas power generation module also comprises an organic ion hydrogel, and the organic ion hydrogel is arranged on the lower surface of the power generation material; The power generation material is a composite aerogel of nanosheets, nanofibers and hydrophilic polymers.
2. The moisture-friction dual-mode power generation device according to claim 1, characterized in that: The mass ratio of the nanofibers to the hydrophilic polymer in the composite aerogel is 100:1 to 1:100; the mass ratio of the nanosheets to the nanofibers is 10:1 to 1:100; The nanosheet is a two-dimensional nanosheet; The two-dimensional nanosheet is one or more of graphene oxide GO, MXene, montmorillonite MMT, and molybdenum disulfide MoS2; the nanofiber is one or more of cellulose nanofiber CNF, aramid nanofiber ANF, and silk nanofiber SNFs; The hydrophilic polymer is one or more of polyvinyl alcohol (PVA), polyacrylic acid (PAA), and polyethylene glycol (PEG); The composite aerogel contains a layered structure, and a directional pore network exists between each layer.
3. The moisture-friction dual-mode power generation device according to claim 2, characterized in that: The directional pores are one of fully-through or semi-through micro-pores, nano-pores, and micro / nano composite pores, and the pores are directional and arranged along the vertical direction.
4. The moisture-friction dual-mode power generation device according to claim 2, characterized in that: The preparation method of the composite aerogel comprises: stirring the nanofiber and the hydrophilic polymer solution uniformly, then adding the nanosheets, stirring and degassing, gelling to obtain a pre-gel, and then freezing and drying to obtain the composite aerogel; Or the nanofibers and hydrophilic polymer solution are stirred evenly, and then the nanosheets are added, stirred evenly, 3D printed, frozen and dried to obtain a composite aerogel; and the height of the composite aerogel power generation material is 1 to 50 mm.
5. The moisture-friction dual-mode power generation device according to claim 4, characterized in that: The solvent of the hydrophilic polymer solution is one or more of deionized water, ethanol, glycerol, acetic acid, and ethyl acetate; The freezing is direct freezing or directional freezing.
6. The moisture-friction dual-mode power generation device according to claim 1, characterized in that: The organic ion hydrogel is arranged on the lower surface of the power generation material: the organic ion hydrogel and the power generation material are directly adhered. The organic ion hydrogel components include gel network matrix materials, inorganic salts and solvents; wherein the gel network matrix materials include any one of polyacrylamide PAM, polyacrylamide PAM / polyvinyl alcohol PVA, polyacrylamide PAM / gelatin GA, and polyacrylamide PAM / polystyrene sulfonic acid PSSA; the inorganic salts include one or more of LiCl, NaCl, MgCl2, AlCl3, KCl, CaCl2, and CoCl2; the solvent is a blended solvent of an organic solvent and water; wherein the organic solvent includes one or more of ethylene glycol, glycerol, and dimethyl sulfoxide DMSO; and the mass percentage of water in the blended solvent is 0.1 to 99.9%.
7. The moisture-friction dual-mode power generation device according to claim 1, characterized in that: The insertion electrodes include a bottom electrode of a wet gas power generation module, an upper electrode of a wet gas power generation module, and a lower electrode of a friction power generation module; The inserted electrode is one or more of an ITO glass electrode, an FTO glass electrode, a TCO glass electrode, and a metal electrode; the friction power generation module also includes a friction contact electrode, wherein the friction contact electrode is arranged directly above the power generation material; The moisture-friction dual-mode power generation device also includes a circuit connector, wherein the circuit connector is a rectifier circuit, wherein the rectifier circuit couples the rectified AC output and DC output in parallel.
8. The moisture-friction dual-mode power generation device according to claim 7, characterized in that: The friction contact electrode includes a conductive tape and a friction functional layer; wherein the conductive tape includes one or more of a conductive cloth tape, a conductive silicone tape, and a conductive metal tape; the conductive component in the conductive tape includes one or more of platinum, gold, silver, copper, nickel, aluminum, carbon materials, graphene, MXene, carbon nanotubes, and conductive polymers; the friction functional layer material includes one or more of polytetrafluoroethylene PTFE, polyperfluoroethylene propylene FEP, polydimethylsiloxane PDMS, polyvinylidene fluoride-co-hexafluoropropylene PVDF-HFP, polyvinylidene fluoride PVDF, polypropylene PP, polyethylene terephthalate PET, styrene propylene copolymer, styrene butadiene copolymer, artificial fiber, polymethacrylate, polyvinyl alcohol, polyethylene glycol, polyester, polyisobutylene, polyethylene terephthalate, chloroprene rubber, butadiene propylene copolymer, natural rubber, polyacrylonitrile, acrylonitrile vinyl chloride, stainless steel sheet, iron sheet, copper sheet, and silver sheet.
9. Application of the moisture-friction dual-mode power generation device according to claim 1 in the fields of environment, energy, information and national defense.
10. The use according to claim 9, characterized in that: The applications in the environmental field include at least one of autonomous collection of environmental energy and application of intelligent environmental detection equipment; the applications in the energy field include at least one of triboelectric energy collection, piezoelectric energy collection, moisture energy collection, autonomous utilization of environmental energy, and quantitative sensing applications; the applications in the information field include at least one of application of environmental perception, sensing and information interaction equipment; the applications in the defense field include application of electrical power supply or power generation equipment in extreme environments.
Citation Information
Patent Citations
Self-energized humidity sensor and preparation method thereof
CN106525910A
Multi-response polyelectrolyte self-generating composite membrane and preparation method thereof
CN114479302A
Integrated wearable transdermal iontophoresis patch powered by moisture generator and preparation method of integrated wearable transdermal iontophoresis patch
CN118576883A
Moisture enabled electric power generation materials and device
US20220407436A1